Nanostructured Fe Rh in metallic and insulating films - Kaeswurm, Barbara; Jimenez-Villacorta, Felix; Bennett, SP; Heiman, Donald; Lewis, Laura H. (Journal of Magnetism and Magnetic Materials, 2014)
The formation of nanostructured FeRh in nonmagnetic metallic and insulating matrices is investigated and correlated with their structural and magnetic properties, with the goal of clarifying synthesis-structure-property relationships in confined geometries. Films containing FeRh with Al2O3 and Cu matrices were deposited on Si substrates using RF sputtering and then annealed up to 1073 K to form chemically-ordered FeRh particles with the B2 structure. FeRh nanostructures formed within the refractory Al2O3 matrix are rounded in shape and have a smaller average particle size of 60 nm, compared to the more irregular nanostructures obtained in the metallic Cu-FeRh sample with a larger average particle size similar to 150 nm The different morphology of the two samples is explained in terms of the dissimilar properties of the matrices, and opens pathways for potential control of the fabrication of FeRh nanostructures. (C) 2013 Elsevier B.V. All rights reserved
Keywords: FeRh; Magneto caloric effect; Magneto structural transition; Ferromagnetism